2000
DOI: 10.1080/j.1600-0412.2000.079005397.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, cellular proliferation and expression of p53 in human uterine leiomyomas and myometrium during the menstrual cycle and after menopause

Abstract: Our findings indicate that sex steroids influence the growth of leiomyomas by stimulating cell proliferation rather than by affecting apoptosis. The rate of cell proliferation is higher in fertile age than after menopause and appears to be enhanced under the influence of progesterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…This is in agreement with previously published data [8][9][10][11]. It has been suggested that the control of growth is regulated differently in the myometrium and leiomyomas and that the proliferative activity in leiomyomas is stimulated by progesterone [6,11]. The concept of hormonal control of proliferative activity is supported by the findings that the menopause and GnRHa therapy greatly reduce the number of mitotic cells [11][12][13].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is in agreement with previously published data [8][9][10][11]. It has been suggested that the control of growth is regulated differently in the myometrium and leiomyomas and that the proliferative activity in leiomyomas is stimulated by progesterone [6,11]. The concept of hormonal control of proliferative activity is supported by the findings that the menopause and GnRHa therapy greatly reduce the number of mitotic cells [11][12][13].…”
Section: Discussionsupporting
confidence: 81%
“…It has been suggested that progesterone may act as a growth-promoting factor in the regulation of leiomyoma growth through enhanced inhibition of apoptosis [3]. However, in a recent study no such differences in the apoptotic index were found between leiomyomas and myometrium, or between the menstrual cycle phases [6]. However, hormonal regulation of apoptosis is likely, since it has been shown that the apoptotic index is very low after the menopause [6] and after GnRHa therapy [12], and that genes coding for Bcl-2 family proteins seem to be related to and influenced by gonadal steroids [5].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These findings are consistent with the lack of morphologic evidence of differences in degree of apoptosis within the tumors and corresponding myometria, either by examination of H&E-stained sections or by the TUNEL technique. A similar lack of difference in apoptotic indices between leiomyomas and myometrium has been observed by other authors [33].…”
Section: Discussionsupporting
confidence: 75%